Recent findings in the regulation of G6PD and its role in diseases - Meng, Qingfei; Zhang, Yanghe; Hao, Shiming; Sun, Huihui; Liu, Bin; Zhou, Honglan; Wang, Yishu; Xu, Zhi-Xiang (Frontiers in Pharmacology, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) is the only rate-limiting enzyme in the pentose phosphate pathway (PPP). Rapidly proliferating cells require metabolites from PPP to synthesize ribonucleotides and maintain intracellular redox homeostasis. G6PD expression can be abnormally elevated in a variety of cancers. In addition, G6PD may act as a regulator of viral replication and vascular smooth muscle function. Therefore, G6PD-mediated activation of PPP may promote tumor and non-neoplastic disease progression. Recently, studies have identified post-translational modifications (PTMs) as an important mechanism for regulating G6PD function. Here, we provide a comprehensive review of various PTMs (e.g., phosphorylation, acetylation, glycosylation, ubiquitination, and glutarylation), which are identified in the regulation of G6PD structure, expression and enzymatic activity. In addition, we review signaling pathways that regulate G6PD and evaluate the role of oncogenic signals that lead to the reprogramming of PPP in tumor and non-neoplastic diseases as well as summarize the inhibitors that target G6PD.